The Performance Investigation of Darrieus Wind Turbine with Adjustable Rotor Diameter : Penyelidikan Prestasi Turbin Angin Darrieus dengan Diameter Rotor Boleh Laras - ABDUL RAZAK, ARIF ASYRAF; ZULKAFLI , MOHD FADHLI (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Wind energy is one of the popular sources of renewable energy that have largely been utilize around the globe. This energy converted kinetic energy into mechanical and electrical energy through application of wind turbine. Generally, wind turbines can be classified into two types which are horizontal axis wind turbines (HAWTs) and vertical axis wind turbines (VAWTs). This paper is concerned with the performance of Darrieus wind turbine with adjustable rotor diameter. This research is conducted to investigate how the rotor diameter of the Darrieus wind turbine effected its performance by analyzing and comparing the power coefficient and torque coefficient produced. In this research, the Darrieus wind turbine has been designed for purposes of simulation process in QBlade software. The actual design of Darrieus wind turbine with adjustable rotor diameter is designed in Solidworks software while the simulation study in QBlade software experimented every 100 mm interval diameter from 500 mm to 1000 mm. The findings from this study shows that different tip speed ratio, TSR require different rotor diameter to produce the highest Cp and Cm. The lower value TSR mostly suited at 500 mm rotor diameter while at higher TSR, 1000 mm rotor diameter give the best performance for the Darrieus wind turbine. Even though the expected performance from simulation study shows positive value of Cp and Cm, there are also some parts of the graph especially from smaller rotor diameter simulation shows negative values of Cp and Cm at certain TSR. Thus, it is necessary to make some improvements to the design and simulation parameters so that it can produce positive and higher values of Cp and Cm to ensure the wind turbine has better performance.